Jumping and the aerial behavior of aquatic mayfly larvae (Myobaetis ellenae, Baetidae). Issue 4 (July 2018) - Yanoviak, Stephen P.; Dudley, Robert
Abstract: Mayfly larvae generally are aquatic, but some madicolous taxa (i.e., living in thin water films) crawl over rocks within streams and waterfalls. When startled, these larvae can break the water film, jump, and enter an aerial phase of locomotion. Because mayfly larvae have been suggested as potential exemplars for the origin of insect wings as tracheal gills, and furthermore represent the most basal extant lineage of pterygotes, we analyzed jumping behavior and free-fall trajectories for one such species of mayfly ( Myobaetis ellenae, Baetidae) in Costa Rica. Jumping was commonplace in this taxon, but was undirected and was characterized by body spinning at high angular velocities. No aerodynamic role for the tracheal gills was evident. By contrast, jumping by a sympatric species of bristletail ( Meinertellus sp., Archaeognatha) consistently resulted in head-first and stable body postures during aerial translation. Although capable of intermittently jumping into the air, the mayfly larvae could neither control nor target their aerial behavior. By contrast, a stable body posture during jumps in adult bristletails, together with the demonstrated capacity for directed aerial descent in arboreal representatives of this order, support ancestrally terrestrial origins for insect flight within the behavioral context of either jumping or falling from heights. Highlights: Larvae of the tropical mayfly M. ellenae voluntarily jump from vertical surfaces. High speed video was used to quantify jump takeoff and subsequent aerial behavior. Jumping was undirected and aerial trajectories were uncontrolled. No aerodynamic role for the tracheal gills was evident. Mayfly aerial behaviors were unlike those of arboreal jumping bristletails.